Value of bioimpedance analysis and anthropometry for complication prediction in children with malignant and non-malignant diseases after hematopoietic stem cells transplantation - G. Ya. Tseytlin; A. Yu. Vashura; M. V. Konovalova; D. N. Balashov; M. A. Maschan1; S. V. Belmer (Онкогематология, 2014)
Hematopoietic stem cell transplantation (HSCT) is widely used in the treatment of malignant and autoimmune diseases. Various complications often develop during the post-transplantation period that can significantly impair the clinical outcomes, so the ability to predict therisk of severe complications is of great practical importance. Predictive value of some anthropometric indices and bioimpedance analysis(BIA) measured before conditioning to assess the risks of serious complications and graft hypofunction in the early post-transplant period(100 days) were analyzed. Anthropometry and BIA used in a comprehensive assessment of nutritional status in order to optimize the nutritional support of these patients. 101 patients were examined before conditioning and at different times during the early post-transplant period: 50 children (5–17 years of age) were examined using BIA and anthropometry, 61 children (6 months – 4 years of age) – using only anthropometry without BIA due to age restrictions. The prognostic value of the phase angle (FA), ratio of the active cell mass to lean body mass (ACM/LBM) and shoulder muscle circumference (SMC) was shown. Thus, in patients with FA ≤ 4, ACM/LBM < 0.45 and SMC ≤ 10th percentile before conditioning risk of severe complications during early post-transplant period was significantly higher (p < 0.05). Also, in patients with FA ≤ 4 and ACM/LBM < 0.45 a significantly higher risk of graft hypofunction developing was observed (p < 0.05).